2021
DOI: 10.1080/00325481.2021.1874166
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the COVID-19 outbreak on physicians’ psychological resilience levels

Abstract: Background: Health care workers exposed to coronavirus19 disease could be psychologically stressed. The objective of this study is to assess the anxiety, depression levels, and psychological resilience of physicians working during the Covid-19 outbreak and to evaluate the related factors that are associated with their psychological resilience. Methods: The sample of this descriptive study was composed of medical doctors and dentists. The data was obtained online between April 13-23, 2020 through a survey prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 46 publications
3
26
1
6
Order By: Relevance
“…Respondents that came into contact with contaminated materials/infected individuals reported higher scores across nearly all COVID-19-associated problem areas than respondents who had no such contact. This has already been shown in similar studies [ 56 ]. Accordingly, it appears critical that frontline healthcare workers should be given priority in relief and support services when treating COVID-19 patients.…”
Section: Discussionsupporting
confidence: 87%
“…Respondents that came into contact with contaminated materials/infected individuals reported higher scores across nearly all COVID-19-associated problem areas than respondents who had no such contact. This has already been shown in similar studies [ 56 ]. Accordingly, it appears critical that frontline healthcare workers should be given priority in relief and support services when treating COVID-19 patients.…”
Section: Discussionsupporting
confidence: 87%
“…Meynaar et al found an increased prevalence of burnout among intensivists, which was inversely correlated to the resilience and work engagement scores 26 . Consistent results were found in Canada, and in Turkey: resilience was an important factor associate with reduced stress and distress during this COVID-19 crisis 27 , 28 .…”
Section: Discussionsupporting
confidence: 81%
“…Results of a study conducted by Huang et al show that the resilience level of the medical staff in the radiology departments during the outbreak of COVID-19 was generally low (26). Several studies have been conducted to investigate the association between selected factors and resilience and to evaluate the potential effect of resilience on psychic symptoms among physicians (27,28). Their results show that resilience level of the physicians was generally low.…”
Section: Resultsmentioning
confidence: 99%